As versões de apoio matricial por um grupo de profissionais de saúde - Silva, Renata Laureano da (2017)
We aim at understanding the versions of Matrix Support (MS) produced by a group of health professionals. The study is based on the discursive practices and meaning construction framework within social constructionism perspective. To achieve our goal, we used two methodological strategies: participation in an extension project about MS and a workshop with health professionals. Information was produced by using field journals and group interviews. Analysis was made based on the construction of dialogic maps and focused on the use of linguistic repertoires. The participation on the extension project made it possible to discuss how relations between health professionals could develop MS actions. Health professionals at the workshop expressed linguistic repertoires related to different MS relations: “between professionals”; “self-experience”; “with public health users”; “with the current model” and “theory versus practice”. The linguistic repertoires used by health professionals were the same used in scientific literature on MS. We understand these repertoires as replies to the researcher herself and her positioning in the workshop. Health professionals name MS a kind of knowledge produced “in between”, not just a sum of random actions. MS is a concept in construction, flexible and light. Flexibility and lightness means the opposite of superficiality: it is necessary to work with unpredictability at the health services. MS is unique and universal, produced in different ways, resulting in different versions which perform multiple realities. These versions change from place to place when perform different practices.